THE DEVELOPMENT OF INFORMATION SYSTEMS IN DOCUMENTATION MANAGEMENT OF EMERGENCYCARE NURSING - Dini Rudini; Fadliyana Ekawaty (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2021)
ABSTRACT Emergency nursing requires prompt, precise, thorough and critical thinking nursing actions. Emergency nurses are often under high pressure, so they sometimes miss documentation of nursing care because it is still manually. Whereas documentation is important as an instrument of communication between professions that contains the status of patient development, patient needs, and activities that have been planned. the documentation process is considered a hassle for nurses because it takes time. Based on this, the researcher wants to develop a software to make it easier for emergency nurses to document nursing care in the emergency unit. The method used at this research is a product-oriented development model. The stages are: 1). Initiation System (initiation of the system), 2). Analysis System, 3). Design System and 4). Production that then tested through the prototype Black Box Testing. The research result shows that this software very useful because it shortens the time for preparing reports. Even this study uses students as research objects, nurses who work in the hospital also can use this software. Keywords: Nursing; technology; information; documentation; Emergency. Abstrak Asuhan keperawatan gawat darurat merupakan tindakan keperawatan yang cepat, tepat, dan memerlukan ketelitian dan pemikiran kritis. Perawat gawat darurat seringkali berada pada kondisi dibawah tekanan yang tinggi, sehingga terkadang melewatkan dokumentasi asuhan keperawatannya karena masih dilakukan secara manual. Padahal dokumentasi penting sebagai instrument komunikasi antar profesi yang berisi status perkembangan pasien, kebutuhan pasien, dan kegiatan yang telah direncanakan dan dilakukan.proses dokumentasi ini dianggap merepotkan bagi perawat karena memerlukan waktu yang lama. Berdasarkan hal tersebut peneliti merasa perlu untuk mengembangkan suatu perangkat lunak sebagai upaya untuk memudahkan perawat IGD dalam mendokumentasikan asuhan keperawatan di ruang IGD. Metode yang digunakan berorientasi pada produk. Penelitian ini melibatkan beberapa ahli materi, ahli media dan pengguna. Teknik analisis data yang digunakan deskriptif kualitatif. Kata Kunci : keperawatan, IGD, Dokumentasi, aplikasi